Geographic variations in vessel and fiber morphology of teak (Tectona grandis Linn.) from Kerala: Implications for wood quality and sustainable forestry - Sushama Raj, R. V.; Varughese, P. M. (Current Botany, 2025)
Teak (Tectona grandis Linn.) is one of the most valuable tropical hardwoods globally, renowned for its exceptional durability, strength, and aesthetic appeal. These attributes make it highly sought after for construction, furniture, and shipbuilding applications. The unique properties of teak are intrinsically tied to its anatomical structure, which influences its physical, mechanical, and hydraulic performance. This study examines the anatomical properties of teak wood collected from seven locations in Kerala, focusing on vessel and fibre morphology to understand how geographic factors influence wood quality. Vessel characteristics such as length, diameter, area, and eco-anatomical indices like mesomorphy and vulnerability reveal significant regional variations, with Nilambur samples demonstrating superior hydraulic efficiency and structural integrity. Fibre traits, including length, width, lumen diameter, and wall thickness, also varied, reflecting environmental and genetic influences. These findings underscore the importance of geographic and ecological factors in shaping wood quality, contributing to sustainable forestry practices and advancements in wood technology.